2019
DOI: 10.21032/jhis.2019.44.1.8
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of Impaired Fasting Glucose and HDL-Cholesterol by Gender and Body Mass Index

Abstract: Objectives: We investigated relation between HDL-cholesterol and the incidence of impaired fasting glucose in obese and normal body weight by gender in Korean adults. Methods: 6,438 subjects aged 40-59 years (2,197 impaired fasting glucose, 4,241 normoglycemia) were selected except the patients with cardiovascular disease and pregnant women using 2016 KNHANES data. We analyzed the relation of impaired fasting glucose and HDLcholesterol by BMI. Results: In both men and women regardless of BMI, who with low HDL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…The results of this study indicate that IFG prevalence was high in male subjects who were employed. This result is similar to the general characteristics of individuals with IFG as found in a previous study [5], and is also similar to the results of a study that showed Korean o ce workers as having various health problems such as diabetes mellitus due to a lack of exercise, poor eating habits, and drinking and smoking [34]. Although the legal working hours per week in South Korea were shortened with the introduction of the 5-day workweek system in 2004, South Korea continues to have the longest work hours in the world [35].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The results of this study indicate that IFG prevalence was high in male subjects who were employed. This result is similar to the general characteristics of individuals with IFG as found in a previous study [5], and is also similar to the results of a study that showed Korean o ce workers as having various health problems such as diabetes mellitus due to a lack of exercise, poor eating habits, and drinking and smoking [34]. Although the legal working hours per week in South Korea were shortened with the introduction of the 5-day workweek system in 2004, South Korea continues to have the longest work hours in the world [35].…”
Section: Discussionsupporting
confidence: 92%
“…Fasting blood glucose levels and obesity are affected by balanced caloric intake rather than daily caloric intake [26]. In addition, the outcome of body mass index (BMI) control through dietary intake and physical activity affects IFG [5]; thus, it is important to choose a balanced diet. Western countries are using strategies to improve individuals' health literacy for managing their blood glucose and utilizing nutritional information on various foods [27,28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations